Characterisation of a novel peptide, Brevinin‐1H, from the skin secretion of Amolops hainanensis and rational design of several analogues. (7th September 2020) - Pei, Xinjie; Gong, Zijian; Wu, Qing; Chen, Xiaoling; Wang, Lei; Ma, Chengbang; Xi, Xinping; Chen, Tianbao; Shaw, Chris; Zhou, Mei
Abstract: As drug‐resistant bacteria have become a serious health problem and have caused thousands of deaths, finding new antibiotics has become an urgent research priority. A novel antimicrobial peptide, named Brevinin‐1H, was identified in the skin secretion of Amolops hainanensis through 'shotgun' cloning. It has broad‐spectrum antimicrobial activity against tested micro‐organisms and has anticancer cell activity. To improve its bioactivity and decrease its cytotoxicity, two structural analogues—Brevinin‐1Ha and Brevinin‐1HY—were designed based on the secondary structure of the natural peptide. Brevinin‐1HY, in which tyrosine substituted Pro 11, had similar activity to the natural peptide against Gram‐negative bacteria and cancer cells, but showed a dramatic increase in haemolytic activity and cytotoxicity at its minimum inhibitory concentration. Brevinin‐1Ha, which transferred the Rana‐box from the C‐terminal to a central position, had significantly decreased haemolytic activity, but also in antimicrobial and anticancer activity. The present data suggest that increasing the proportion of α‐helix structure in an AMP can increase its target micro‐organism bioactivity to some extent. Abstract : A novel antimicrobial peptide, named Brevinin‐1H, was identified in the skin secretion of Amolops hainanensis through 'shotgun' cloning. It has broad‐spectrum antimicrobial activity against tested micro‐organisms and has anticancer cell activity. To improve its bioactivity and decrease its cytotoxicity, two structural analogues—Brevinin‐1HF and Brevinin‐1HY—were designed based on the secondary structure of the natural peptide. The present data suggest that increasing the proportion of α‐helix structure in an AMP can increase its target microorganism bioactivity to some extent.